Transaction Data Tests of S&P 100 Call Option Pricing - Sheikh, Aamir M. (Journal of Financial and Quantitative Analysis, 1991)
This paper examines the pricing of S&P 100 calls using 14 months of transactions data. We find that market prices of S&P 100 calls differ systematically from Black-Scholes values. The biases in Black-Scholes model prices are both statistically and economically significant and correspond to biases that arise if market prices incorporate a stochastically changing volatility of the index.